2013
DOI: 10.1002/bse.1805
|View full text |Cite
|
Sign up to set email alerts
|

Recipes for Successful Sustainability: Empirical Organizational Configurations for Strong Corporate Environmental Performance

Abstract: We examine 45 existing case studies of firms with strong corporate environmental performance (CEP) to empirically identify four organizational configurations for successful sustainability. These four configurations represent different combinations of variables describing a firm's external environment, organizational structure, and its strategy-related activities. More specifically, these configurations vary in having a benign or challenging external environment, a mechanistic or organic structure, a low-cost o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 81 publications
(112 reference statements)
1
43
0
Order By: Relevance
“…Maggetti (2014) analyzes firm-level organizational factors that explain participation in multistakeholder agreements establishing principles against money laundering. Walker et al (2015) study how configurations of external environments, firm organizations, and strategies explain corporate environmental performance. Other articles use QCA to investigate the relationship between different types of CSR practices and corporate performance.…”
Section: Discussionmentioning
confidence: 99%
“…Maggetti (2014) analyzes firm-level organizational factors that explain participation in multistakeholder agreements establishing principles against money laundering. Walker et al (2015) study how configurations of external environments, firm organizations, and strategies explain corporate environmental performance. Other articles use QCA to investigate the relationship between different types of CSR practices and corporate performance.…”
Section: Discussionmentioning
confidence: 99%
“…Yet increasingly scholars find that allowing companies greater flexibility in crafting their own environmental policies may allow for greater innovation and creativity than a one‐size‐fits‐all regulatory model (e.g. Walker et al , ). This evidence suggests that the role of public policy may lie in providing incentives to companies, rather than quotas or mandates, that encourage, recognize and reward companies for gender diversity and environmental practice.…”
Section: Discussionmentioning
confidence: 99%
“…Scholarship on the predictors of corporate social responsibility and environmental performance has analyzed several factors that shape corporate practice (e.g. Walker et al , ). This scholarship provides evidence that organizational diversity – particularly among decision makers – enhances corporate social responsibility (CSR) efforts and recognition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has also shown that environmental responsibility varies by industry (Berrone et al , ; Brammer and Pavelin, ; Fifka, ; Lee et al , ; Koh et al , ). Despite burgeoning research on the relationship between industrial factors and corporate environmental responsibility, only a couple of studies have taken into account the impact of the general industry context (for instance, Goll and Rasheed, ; Rothenberg and Zyglidopoulos, ; Walker et al , ). Goll and Rasheed () examined the contingent role of industrial munificence and dynamism in the relationship between CSR and firm financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Goll and Rasheed () examined the contingent role of industrial munificence and dynamism in the relationship between CSR and firm financial performance. Rothenberg and Zyglidopoulos () focused on the printing industry and measured the dynamism and munificence at the state level to explain the determinants of environmental innovation, while Walker and his colleagues () drew on configuration theory to identify how the organizational configurations interact with each other and influence environmental performance. We extend this approach to investigate the links between three distinct characteristics of industry context and corporate environmental responsibility, namely munificence, dynamism, and complexity (Aldrich, ; Dess and Beard, ).…”
Section: Introductionmentioning
confidence: 99%